Modeling optical second harmonic generation for oxide/semiconductor interface characterization. (January 2023) - Mallick, Binit; Saha, Dipankar; Datta, Anindya; Ganguly, Swaroop
Abstract: In this work, we present physics-based numerical modeling of experimental time-dependent optical second harmonic generation data from an oxide/semiconductor (SiO2 /Si) interface. A comprehensive numerical solution to the Poisson–Boltzmann equation has been developed here, using the Newton–Raphson method at different time instances. It incorporates the trapping behavior of photo-excited charge carriers at the silicon dioxide/silicon (SiO2 /Si) interface, within the silicon dioxide (SiO2 ) and at the SiO2 surface, in order to model the second harmonic photon count data obtained from our in-house experimental setup. This yields a quantitative analysis of the SiO2 /Si interface, oxide, and surface charge densities, and provides a contact-less and non-invasive optical technique for oxide/semiconductor interface characterization. Highlights: Contactless and non-destructive oxide/semiconductor interface characterization. Modeling of time-dependent second harmonic generation from SiO2 /Si interface. Poisson–Boltzmann solution for time dependent charge trapping. Quantitative analysis of SiO2 /Si interface and SiO2 surface charge densities. Determination of band bending direction at SiO2 /Si interface on a contactless sample.